Bulgaria : Staff Report for the 2013 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This Informational Annex highlights that the World Bank has been leading the policy dialogue in structural and institutional reforms aimed at Bulgaria's successful European Union (EU) integration and convergence. The Country Partnership Strategy of the World Bank maintains a strong focus on Bulgaria making the most of its EU membership. It aims to partner with Bulgaria in strengthening national institutions and capacity to meet EU targets and in accelerating the absorption of EU grant funds. The World Bank also continues to undertake substantial knowledge and advisory services on policy reforms in selected sectors and themes of Bulgaria's National Reform Program 2011-15, such as innovation, education, business regulation, transportation, water, climate change, and social inclusion.